Study of Mechanical Behavior and Deformation Field Characteristics of Sandstone under Cyclic Loading. (11th April 2023) - Zhong, Anhai
Abstract : The sandstone yield strength and tensile strength were increased under cyclic loading paths by using the Brazilian splitting method. The experiment shows that (1) the sandstone specimens exhibit multiple penetrating crack damage by cyclic loading, while the tensile strength slightly increases; (2) the sandstone horizontal strain (Exx ) concentration area decreases, and the shear strain (Exy ) concentration area increases under cyclic loading, and the damage form changes from completely brittle tensile damage to ductile mixed tensile-shear damage; (3) the mechanism of the increase in tensile strength of the specimen under cyclic loading was explained by digital image correlation (DIC) technique. The results indicate that a time lag occurs in the horizontal strain concentration zone, and the area of the penetration zone decreases from the cyclic loading effect, while the reduced stress concentration leads to increased tensile strength of the specimens.